Stability of corneal endothelial monolayers in the presence of magnetic particles in a rotating magnetic field - Jessica Chin; Leah A. Marquez-Curtis; Mehdi Ghaffari Sharaf; Janet A. W. Elliott; Larry D. Unsworth (PLoS ONE, 2026)
Magnetic particles have significant potential as novel theranostics due to the relative ease of surface modification for targeting molecules or regions of diseased tissues, coupled with remote in vivo manipulation using an exogenous magnetic field. Employing magnetic particles within the eye is hindered by the lack of safety studies. In particular, our lab has developed peptide-conjugated iron-oxide magnetic particles that target and liberate pseudoexfoliation materials from anterior lens capsules under a rotating magnetic field. Further application of such a mode of therapy may hold the key to reducing the incidence of open-angle glaucoma but requires an evaluation of its potential cytotoxic effects on delicate ocular tissue like the cornea, where a disruption of the endothelial cells can cause blindness. To this end, the effects of peptide-conjugated magnetic particles in a low-frequency rotating magnetic field on cultured porcine corneal endothelial cell monolayers was characterized using membrane integrity assessments for cell viability, metabolic activity assay, and ZO-1 immunocytochemical staining. It was observed that magnetic particles under the influence of this magnetic field had no significant immediate or delayed effect on membrane integrity or metabolic activity of corneal endothelial cell monolayers in culture. Moreover, the expression of the ZO-1 tight junction protein was maintained in the monolayers following magnetic treatment. All results support the safe application of 1-µm magnetic particles (0.2 µg/µL) and a rotating magnetic field (5.5 Hz and 0.5 T) for up to 3 hours as a novel therapy for pseudoexfoliation glaucoma.